Answer:
x = 3 , y = 7
Explanation:
Solve the following system:
{8 x - 4 y = -4
x = y - 4
Hint: | Perform a substitution.
Substitute x = y - 4 into the first equation:
{8 (y - 4) - 4 y = -4
x = y - 4
Hint: | Expand the left hand side of the equation 8 (y - 4) - 4 y = -4.
8 (y - 4) - 4 y = (8 y - 32) - 4 y = 4 y - 32:
{4 y - 32 = -4
x = y - 4
Hint: | Choose an equation and a variable to solve for.
In the first equation, look to solve for y:
{4 y - 32 = -4
x = y - 4
Hint: | Isolate terms with y to the left hand side.
Add 32 to both sides:
{4 y = 28
x = y - 4
Hint: | Solve for y.
Divide both sides by 4:
{y = 7
x = y - 4
Hint: | Perform a back substitution.
Substitute y = 7 into the second equation:
{y = 7
x = 3
Hint: | Sort results.
Collect results in alphabetical order:
Answer: {x = 3 , y = 7